THE QUARTER-LIFE CRISIS EXPERIENCED BY MEGAN IN LYNN SHELTON’S LAGGIES - Hidayah, Atika Nur (LANTERN (Journal on English Language, Culture and Literature), 2016)
Laggies (2014) is an independent movie directed by young director Lynn Shelton and writer Andrea Siegel. Laggies tells the story of Megan who experiences quarter-life crisis. Quarterlifecrisisisaperiodof constantchange,instability,andidentityconfusion.Ithitsyoungadultintheageofearly20suntilearly30swheretheadolescencetransformsintotheadulthood.InthemovieLaggies,themaincharacter,Megansuffersfromquarter-lifecrisisinwhichsheisinhermid-20sbutshe does not know what she wants to do for her future. In this thesis, thewriter will describe the intrinsic aspects, which are narrative and cinematography elementsand extrinsic aspect of the movie which is the quarter-life crisis experienced by the character.The objective of this study is to explain the quarter-life crisis experienced by the character inthe movie Laggies. The method used in collecting the data is library research while theapproach used is exponential approach to describe the intrinsic aspects and socialpsychological approach to describe the extrinsic aspects. The result of this thesis is thatMegan in the movie Laggies has finally overcome her quarter-life crisis and lived accordingto her interest and values of life.